Assessment of Low-Grade Meniscal and Cartilage Damage of the Knee at 7 T: A Comparison to 3 T Imaging With Arthroscopic Correlation. Issue 7 (July 2018) - Friebe, Björn; Richter, Martin; Penzlin, Susanne; Stärke, Christian; Kropf, Siegfried; Lohmann, Christoph; Fischbach, Frank; Speck, Oliver
Abstract : Objectives: The aim of this study was to compare the assessment of low-grade meniscal tears and cartilage damage in ultrahigh-field magnetic resonance imaging (MRI) at 7 T to routine clinical MRI at 3 T. Materials and Methods: This study was approved by the local ethics committee, and written informed consent was obtained from each patient. Forty-one patients with suspected meniscal damage or mild osteoarthritis (Kellgren-Lawrence score, 0–2) received 7 T as well as routine clinical 3 T consecutively. The imaging protocol at both field strengths consisted of PD-weighted imaging with more than doubled resolution at 7 T. Images were read blinded regarding field strength and patient characteristics by 3 readers with different experience in musculoskeletal MRI (3 years, 6 years, and 10 years) according to a modified whole-organ MRI score of the knee in osteoarthritis and the Score of the International Cartilage Repair Society. Arthroscopic reports as a criterion standard were available for 12 patients. A multifactorial mixed model analysis was performed. Results: The mean cumulated diagnostic score at 7 T was significantly closer to the criterion standard compared with 3 T in patients where criterion standard was available ( P < 0.001). In all 41 patients, the damages were rated more severely at 7 T reflected by a mean higher cumulative score in cartilage ( P < 0.001) and in the meniscus ( P < 0.001). No difference in interreader variability between 3 T and 7 T was observed. Imaging acquisition time was nearly identical. Conclusions: Morphologic imaging of cartilage and meniscal damage of the knee in ultrahigh-field MRI at 7 T with PD-weighted TSE sequences seemed to have a significantly higher diagnostic accuracy than 3 T and can be performed with equal acquisition times while exploiting higher resolution of 7 T. Abstract : Supplemental digital content is available in the text.